Sun-protective Properties of Technical Sportswear Fabrics 100% Polyester: The Influence of Moisture and Sweat on Protection against Different Biological Effects of Ultraviolet (UV) Radiation - Aguilera-Arjona, José; Navarrete-de-Gálvez, Enrique; Sánchez-Roldán, Cristina; Herrera-Ceballos, Enrique; De-Gálvez-Aranda, María Victoria (Wiley, 2022)
The use of technical sportswear is now widespread, but the degree of protection these fabrics offer against UV radiation is not known. We have analyzed the capacity of different types of technical sportswear fabrics to protect against different UV biological effects. A sample of 34 100% polyester t-shirts from different manufactures was classified by color, fabric structure, cover factor, and due to different tonalities, dark, and clear color. Ultraviolet protection factor was calculated according to UNE-EN13758. The protection factor for other biological effects as pre-vitamin D3 production, non-melanoma skin cancer, photoimmunosuppression, and photoaging was analyzed. The effects of moisture and sweat in protection were also evaluated. From the analyzed sample garments, more than 75% achieved an excellent protection value (protection factor 40–50+). Higher values were found in double-layer type (P < 0.05). Cover factor was the main determinant of biological protection factors with correlation coefficients of 0.81 for UPF (erythema), 0.77 for NMSC, and 0.63 for photoimmunosuppression. Water or sweat humidity saturation increased biological protection factors over a 20% (P < 0.05). The 83% of the fabrics analyzed showed less than 5% of transmittance with labeling as UVA protective elements. No effect of fabric color was found related to biological protection factors. The 100% polyester sports T-shirts of the analyzed sample offer general protection against UV for different biological effects that can be increased by humidity but no affected by fabric color.
Keywords: Radiación solar; Sun-protective; Polyester; Ultraviolet (UV) Radiation